The Assyrian Dictionary of the Oriental Institute of the University of Chicago. Vol. 8: K (1971)
Editorial Board: Miguel Civil, Ignace J. Gelb, A. Leo Oppenheim, Erica Reiner (A. Leo Oppenheim, Editor-in-Charge; Erica Reiner, Editor; Robert D. Biggs, Associate Editor; with the assistance of Johannes M. Renger, Ronald F. G. Sweet, and David B. Weisberg; Assistant to the Editors: Marjorie Elswick).